NeuroVault.org: a web-based repository for collecting and sharing unthresholded statistical maps of the human brain - Gorgolewski, Krzysztof J.; Varoquaux, Gael; Rivera, Gabriel; Schwarz, Yannick; Ghosh, Satrajit S.; Maumet, Camille; Sochat, Vanessa V.; Nichols, Thomas E.; Poldrack, Russell A.; Poline, Jean-Baptiste; Yarkoni, Tal; Margulies, Daniel S. (Frontiers in Neuroinformatics, 2015)
Here we present NeuroVault — a web based repository that allows researchers to store, share, visualize, and decode statistical maps of the human brain. NeuroVault is easy to use and employs modern web technologies to provide informative visualization of data without the need to install additional software. In addition, it leverages the power of the Neurosynth database to provide cognitive decoding of deposited maps. The data are exposed through a public REST API enabling other services and tools to take advantage of it. NeuroVault is a new resource for researchers interested in conducting meta- and coactivation analyses.